In Vivo Distribution and Therapeutic Efficacy of Radioiodine-Labeled pH-Low Insertion Peptide Variant 3 in a Mouse Model of Breast Cancer - Min Zhang; Yue Xi; Hong Chen; Wangxi Hai; Biao Li (Molecular Imaging)
Purpose. Extracellular acidity is a marker of highly aggressive breast cancer (BC). pH-low insertion peptides (pHLIPs) target the acidic tumor microenvironment. This study evaluates the distribution and therapeutic efficacy of radioiodine-labeled pHLIP variant 3 (Var3) in a mouse model of BC. Methods. The binding of fluorescein isothiocyanate (FITC)- or radioiodine-125 (125I) labeled Var3-pHLIP to MDA-MB-231, 4T1, and SK-BR-3 BC cell lines under different pH values was evaluated in vitro. The distribution of 125I-labeled Var3-pHLIP and wild-type- (WT-) pHLIP in tumor-bearing mice was analyzed in vivo using micro-SPECT/CT imaging. The therapeutic efficacy of radioiodine-131 (131I)-labeled Var3-pHLIP in MDA-MB-231 xenografts was evaluated by relative tumor volume measurement and immunohistochemical analysis. Results. The binding ability of FITC- or 125I-labeled Var3-pHLIP to tumor cells increased with the decrease in pH. The tumor-to-background ratio of 125I-Var3-pHLIP in BC xenografts showed the best imaging contrast at 24 h or 48 h postinjection. The uptake of 125I-Var3-pHLIP in MDA-MB-231 xenografts at 2 h postinjection was significantly higher than that of 125I-WT-pHLIP (3.76±0.37 vs. 2.87±0.60%ID/g, p=0.046). The relative tumor volume in MDA-MB-231 xenografts was significantly lower in the 131I-Var3-pHLIP-treated group than in the groups treated with Var3-pHLIP (p=0.027), 131I (p=0.001), and saline (p<0.001). The 131I-Var 3-pHLIP group presented a lower expression of Ki67 and a higher expression of caspase 3. Conclusion. Radioiodine-labeled Var3-pHLIP effectively targeted BC cells in an acidic environment and inhibited the growth of MDA-MB-231 xenografts by ionizing radiation.